2021
DOI: 10.53366/jimki.v9i1.338
|View full text |Cite
|
Sign up to set email alerts
|

Faktor – Faktor Terkait Tingkat Keparahan Infeksi Coronavirus Disease 2019 (COVID-19): Sebuah Kajian Literatur

Abstract: Pendahuluan: Pandemi penyakit virus corona (COVID-19) 2019 yang mulai mewabah pada awal tahun  2020 memicu ditetapkannya Public Health Emergency of International Concern (PHEIC) oleh WHO. Disebabkan oleh SARS-CoV-2, COVID-19 memiliki utamanya menginfeksi sistem pernafasan dengan menempel pada reseptor ACE2. Infeksi COVID-19 menyebabkan beragam manifestasi klinis mulai tanpa gejala hingga gejala berat yang mengancam nyawa bergantung pada berbagai faktor. Berbagai faktor yang mampu menentukan berat-ringannya man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…These results align with research conducted by Cheng et al (2020), which found an average patient age of 63 years from the 701 samples studied (16). This research variable can prove that with age, a degenerative process can affect a person's health through a decrease in the quantity and quality of the immune system (17).…”
Section: Discussionmentioning
confidence: 89%
“…These results align with research conducted by Cheng et al (2020), which found an average patient age of 63 years from the 701 samples studied (16). This research variable can prove that with age, a degenerative process can affect a person's health through a decrease in the quantity and quality of the immune system (17).…”
Section: Discussionmentioning
confidence: 89%
“…Penyakit baru, yang disebabkan oleh virus corona tidak teridentifikasi hingga desember 2019 ketika muncul di wuhan, china (who,2020). Indonesia adalah salah satu negara dengan jumlah kasus covid-19 terbanyak ke-20 dan negara indonesia mengkonfirmasi kasus covid-19 pada 2 maret 2020, terdapat 743.198 kasus pasien positif, 611.097 pasien sembuh, 22.138 pasien meninggal dunia, sehingga pasien aktif dari tanggal 2 maret sampai dengan 31 desember 2020 tercatat kasus sebanyak 109.963 orang (BNPB, 2020). Provinsi Bali mengkonfirmasi sebanyak 17.745 kasus, transmisi lokal sebanyak 17.229 orang, dan pasien meninggal sebanyak 523 orang.…”
Section: Pendahuluanunclassified
“…Meanwhile, 143,270 deaths have occurred in Indonesia. In Indonesia, national data has recorded that more than 11 thousand children have lost their parents due to Covid-19 (Azizah et al, 2023;Haq et al, 2021). The outbreak of the Covid-19 virus has also caused anxiety in the community and has hurt the mental health of those who experience it (Ilpaj & Nurwati, 2020;Maulida et al, 2020).…”
Section: Introductionmentioning
confidence: 99%